Comparative study of symmetrical OTA performance in 180 nm, 130 nm and 90 nm CMOS technology - Wan Mohammad Ehsan Aiman bin Wan Jusoh; Siti Hawa Ruslan; Nabihah Ahmad; Warsuzarina Mat Jubadi; Rahmat Sanudin (Institute of Advanced Engineering and Science, 2019)
In this paper, the comparative study of symmetrical Operational Transconductance Amplifier (OTA) performance between 180 nm, 130 nm and 90 nm CMOS technology have been done thoroughly to find the relationship between voltage supply and bias current with performance parameters (gain, power consumption and Common-Mode Rejection Ratio (CMRR)). The OTA which adopts symmetrical topology is designed carefully and simulated using Synopsys HSpice software and the results are carefully analyzed and compared. The symmetrical OTA designed in 90 nm CMOS technology is found to be the best because the power consumed is only 9.83 µW from ±0.9 V voltage supply and the OTA achieved 55.9 dB of the DC gain. The CMRR of the symmetrical 90 nm OTA is 140 dB which is sufficient to reject the common-mode signals in electrocardiogram (ECG) input signal. The symmetrical 90 nm OTA is suitable to be implemented as bioamplifier in ECG signal detection system as it consumed low power and has a high CMRR characteristic.